Indonesia Basketball League: Spectators's Perception of CSE Satisfaction - Dally Nur Arif; Muhamad Hafidz Ali Mashum; Alya Farah (Tinta Emas Institute, 2024)
Spectators are a major part and are very important in a sporting event. The number of spectators will affect the broadcasting rights, advertisements, and sponsorships for the event and is the key to success. This study investigating how spectators perceived CSE’s on Indonesian Basketball League 2022-2023. We dissect the values on six indicators: perceived prosocial impact, value quality, knowledge attainment, sense of community, trust in CSE, and entertainment value. A total of 332 respondents were willing to be participants in this study. The data analysis method used is multiple linear regression analysis. The result shown that large influence from entertainment value and perceived prosocial impact, it also has an impact on the perception of other indicators so that it has a positive influence. Despite being a medium and small indicator, trust in CSE, Value quality, Knowledge attainment, and Sense of community can be an opportunity for planning the IBL organization in the next season.